Randomised, cross-over trial on the effect of isotonic and isometric exercise on pain and strength in proximal hamstring tendinopathy: trial protocol. Issue 1 (5th January 2021) - Rich, Aidan; Cook, Jilliane Leigh; Hahne, Andrew John; Rio, Ebonie Kendra; Ford, Jon
Abstract : Background: Proximal hamstring tendinopathy (PHT) is a condition that occurs at all ages and levels of sporting participation. Presenting as localised lower buttock pain with tasks such as squatting and sitting, it can cause disability with sport, work and other activities of daily living. Recent research has investigated the effect of isometric exercise on pain and strength with a range of tendinopathies but there are no published studies on PHT. This protocol paper details a study investigating the effectiveness of isometric compared with isotonic exercise on pain and strength in people with PHT. Methods/Design: The study is a prospective, cross-over randomised controlled trial (RCT). Twenty participants with PHT, recruited from the local community and sporting clubs will be recruited for the study. Participants will receive one session of isotonic hamstring strength exercises and one session of isometric hamstring exercise, with random allocation to the order of intervention. Primary outcomes will be hamstring strength measured with a dynamometer and pain with a functional task, assessed immediately following and 45 min after intervention. A secondary outcome will be pain with sitting assessed 24 hours after intervention. The effect of isotonic versus isometric exercise on hamstring pain and strength will be determined using a repeated measures linear mixed model. Further analyses will determine the proportion of patients with clinically important pain and strength improvements, using relative risks, χ 2 testing and number needed to treat. Discussion: This RCT protocol will investigate the effect of isometric compared with isotonic exercise for PHT.